Characteristics of Acute Diarrhea Patients in Toddlers at Ibnu Sina YW-UMI Hospital Makassar in 2021-2022 - Anisah, A. Vania Nurul; Arsal, Andi Sitti Fahira; Darussalam, A. Husni Esa; Jafar, Muh. Alfian; Darma, Sidrah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Acute diarrhea is defined as passing stool more than 3 times a day with a change in consistency to liquid, with or without mucus and blood, and lasting less than one week. Diarrhea remains an endemic disease and a significant contributor to mortality in Indonesia, especially among toddlers.The purpose of this research is to determine the characteristics of acute diarrhea patients in toddlers at Ibnu Sina Hospital Makassar in 2021-2022. The results showed the highest incidence of acute diarrhea found in the age group of 1 - <3 years (53.1%), predominantly in males (53.1%), with good nutritional status (60.5%), experiencing vomiting symptoms (41.5%), experiencing dehydration (75.3%), and receiving exclusive breastfeeding (51.9%). The findings of this research lead to the conclusion that acute diarrhea in toddlers is most prevalent in the age group under three years old, predominantly in males, with good nutritional status, experiencing vomiting symptoms, suffering from dehydration, and receiving exclusive breastfeeding.